SIMULASI PEMILIHAN RUTE TERBAIK PADA ROUTING PROTOCOL EIGRP DENGAN MENERAPKAN IPV6 BERDASARKAN PARAMETER BANDWIDTH DAN DELAY - , MAYASARI SURAYYA DEWI; , Sri Suning Kusumawardani, ST., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Exhaustion of Internet Protocol version 4 (IPv4) address, made the Internet Protocol version 6 (IPv6) designed to be implemented to an organizationâs network. Beside an Internet Protocol, network also require a routing protocol. One of the distance vector routing protocol is Enhanced Interior Gateway Routing Protocol (EIGRP). The purpose of this research is to design an expansion of network topology in NUSAMIGAS company and simulate EIGRP routing protocol which implement IPv6 addressing and observe the effect of EIGRPâs parameter such as bandwidth and delay parameters on routes that used to reach destination. There are some steps for finishing this research, such as topology design, configuration and address allocation, simulation, and analysis. The first step in this research is designing a network topology of oil and gas Company called NUSAMIGAS which implementing EIGRP routing protocol and IPv6 addressing. The next step, is implementing EIGRP routing protocol and IPv6 addressing to all network devices. The last step in this research is execute the simulation and analysis to observe the effect of EIGRPâs parameters when using the best routes to reach network destination. Based on this simulation and analysis that has been done in NUSAMIGAS network topology, there are some important result. The time for EIGRP to reach the convergent states is 30,280 second. The best route that used by EIGRP routing protocol to reach destination is effected by bandwidth and delay parameters. Reliability and load parameters are not tested in this research. EIGRP choose the best route which has the smallest metric with the biggest bandwidth and the minimum delay accumulations. EIGRP also used feasible distance, successor, feasible successor, and reported distance to choose the best routes to reach destination.